Peningkatan Keterampilan Komunikasi bagi Pemandu Wisata lokal di Desa Penyanggah Taman Nasional Bromo Tengger Semeru (TNBTS) Wonokitri Pasuruan Jawa Timur - Widianto, Ahmad Arif; Fatanti, Megasari Noer; Ananda, Kun Sila; Meiji, Nanda Harda Pratama; Kodir, Abdul; Dini, Alya Muflihatud (Journal of Dedicators Community, 2022)
This service activity aims to improve the capability of local tour guides in buffer villages in the Bromo Tengger Semeru National Park (TNBTS) area. One of the locations chosen by the Service team is Wonokitri Village, which is located close to the tourist destination of Mount Bromo. Based on the results of field observations, there are several problems why Wonokitri Village is only able to survive as a 'transit village' which is indicated by the low occupancy of tourists staying at local guest houses. This is due to the low communication skills of local tour guides to attract both domestic and foreign tourists to stay longer in Wonokitri Village. In fact, based on the narrative of local residents, they are trying to develop other tourist objects that are expected to be able to support the local economy. Through this service activity, the Proposing Team arranged a series of mentoring and training activities for members of the Tourism Awareness Group (Pokdarwis) in Wonokitri Village, Tosari District, Pasuruan Regency. The service activities consist of first, training in communication skills for tour guides and tourism actors (owners of guest houses, stalls, and souvenir sellers). Second, assistance in making social media as a promotional media, branding as well as local tourism marketing. Finally, thirdly, English language skills training in the context of tourism for tour guides and other tourism actors. The outputs of this activity are publications in the mass media, activity documentation, scientific articles presented at national seminars, and scientific articles published in accredited national journals.